KRITIK ADJIDARMA DALAM EMPAT CERPEN: TENTANG GENDER DAN KELIYANAN - Resti Nurfaidah (SUAR BETANG, 2017)
Seno Gumira Ajidarma is well-known as a multitalented popular figure in Indonesia. He is an artist, a humanist, a writer, an academician, and others. His works are always in excellent quality. They need an incredible depth level of intrinsic aspect exploration. Previous studies have shown that criticism against government of the New Ordermassively appears on Ajidarma’s writting. However, the criticism is well-hidden behind his expertise in word processing and stories composing or other excellent quality works. This research is aimed into Ajidarma's social critique in the following four short stories: “Pelajaran Mengarang”, “Sepotong Senja untuk Pacarku”, “Telinga”, dan “Maria” which are focused on the concept of gender and Other's conflict. Based on the concepts of the Holmes gender and the Other of Callavaro, as well as several supporting references, it comes into the following outcomes: gender conflicts are connected to inferiority and superiority; the non-acceptancy of certain criteria and many causes make the inferior is victimizedwith the arbitrariness of the ruler in such forms: doctrine, alienation, discrimination, detention, torture, even murder; inferiority is resembling the present situation and conditions in this country